Web-Based Application for Single Elimination Tournament Using Linear Congruential Generator - Rakhmadi, Aris; Nugroho, N (Universitas Muhammadiyah Surakarta, 2016)
Sport develops in various branches through various tournaments and is generally organized in the drawing mechanism. The process of drawing is to determine the opponent for each participant. The purpose of this study was to facilitate the organizing committee to manage the data participants and to draw the single elimination diagram match. Other purposes were to facilitate participants to gather information and to register the information via online system. Analysis of requirement formulated the needs of the system. The result of the analysis determined the concept of admin and user use case. The admin has some privileges in the selection and seed priorities of the participants. Subsequently, the system drew and randomised the scheme chart based on the seed category. This research had produced a web-based drawing application which was useful to support each single elimination tournament including of information, registration, and drawing process.